Service Quality and Customer Satisfaction: An Empirical Investigation on Public Sector Banks in Odisha - Patra, Soumendra Kumar; Dash, Ajitab (Journal of Research in Marketing (ISSN: 2292-9355), 2014)
The emergence of liberalization and globalization opened a new paradigm of banking system in India. Now a days, Banks have to deal with many customers and render various types of services to its customers and if the customers are not satisfied with the services provided by the banks then they will defect which will impact economy as a whole. It has become imperative for both public and private sector banks to perform to the best of their abilities to retain their customers by catering to their needs. Many a times it happens that the banks fail to satisfy their customers, which can cause huge losses for banks and there the need of this study arises. In light of this, the present study focuses on the issue of assessment of service quality of Public sector banks in catering to the need of rural masses of the coastal districts of Odisha i.e., Balasore and Bhadrak. This paper used the popular multi-itemed rating scale namely SERVQUAL (developed and modified by Parasuraman et al in 1985,1988, 1991 and 1994) to assess the quality of service rendered by the selected banks. Thereafter, multiple regression analysis is used to anticipate the impact of the quality dimensions, viz. tangibility, reliability, responsiveness, assurance and empathy on customer satisfaction.